A study on modified accelerated diagnostic protocol to safely discharge low-risk chest pain patients in emergency department - Yean, Kok Siew; Abd Wahab, Mahathar; Zakaria, Mohd Idzwan (SAGE Publications, 2020)
Background: Evaluation of chest pain patients in emergency departments to distinguish between high-risk patients who require admission and low-risk patients who can be managed as outpatients is a challenging task. Objective: The aim of this study was to evaluate the efficacy of Observation Ward Short Stay Evaluation Service for Chest Pain Protocol to identify and safely discharge low-risk patients with low incidence of major adverse cardiac events within 30 days. Methods: This was a single center prospective observational study, conducted from 1 March 2016 to 31 August 2016 at the Emergency and Trauma Department, Hospital Kuala Lumpur, Kuala Lumpur. Observation Ward Short Stay Evaluation Service for Chest Pain Protocol was used to evaluate patients presented with chest pain or angina equivalents. The components involved Thrombolysis in Myocardial Infarction (TIMI) score, serial electrocardiograms, high-sensitivity cardiac troponin T, and exercise treadmill test. Low-risk patients were patients with TIMI < 2, normal serial electrocardiogram, high-sensitivity cardiac troponin T ≤ 14 ng/L, and negative exercise treadmill test. If anyone of the components was not fulfilled patients were considered as high risk, and they were either admitted or referred to clinic for further intervention. Low-risk patients were allowed for discharged. All patients were followed-up in 30 days for any incidence of major adverse cardiac events. Results: Totally, 174 patients were studied. Observation Ward Short Stay Evaluation Service for Chest Pain Protocol managed to discharge 102 (58.6%) patients, and 84 (82.4%) of them underwent exercise treadmill test. About 46 (54.8%) patients had negative exercise treadmill test, whereas 38 (45.2%) patients had either positive or inconclusive exercise treadmill test, and they were referred to physician clinic for further cardiac assessment. None of the patients with negative exercise treadmill test developed major adverse cardiac events in 30 days. The sensitivity and the negative predictive value (NPV) of Observation Ward Short Stay Evaluation Service for Chest Pain Protocol were both 100%. Conclusion: Observation Ward Short Stay Evaluation Service for Chest Pain Protocol can be applied in emergency departments to identify and safely discharge patients with low risk of major adverse cardiac events in 30 days. © The Author(s) 2019.